Destination Competitiveness and Sustainability of Cultural Tourism: A Qualitative Study of Malin Kundang Stone Tourism at Air Manis Beach, Padang - Ahmad Putra; Yulia Fitria; Nora Afnita; Febriyeni Nasrul (Dampeng: Journal of Art, Heritage and Culture, 2026)
This study aims to analyze the existence of Batu Malin Kundang Tourism in the competition of tourism destinations in West Sumatra through a field study in the Air Manis Beach area, Padang City. The presence of various new tourist destinations based on natural tourism and modern visual spots creates a competitive dynamic that influences tourist visit patterns. Therefore, it is important to examine how tourist destinations based on local legends and culture can maintain their existence amidst the diversity of new tourism that introduces its beauty. The author uses a descriptive qualitative approach with a field study method. Data were obtained through direct observation, interviews with traders, local residents, and tourists. The results of the study indicate that, first, the existence of Batu Malin Kundang rests on the strength of cultural values ??and legends that have historical legitimacy in the Minangkabau community, second, the main attraction of this destination lies in the symbolic and educational aspects that distinguish it from new tourist destinations that are more oriented towards visual trends, third, the shortcomings of Batu Malin Kundang tourism lie in the innovation side, less active digital promotion, less clean facilities, relatively expensive game rental prices, and rampant extortion. These conditions ultimately become challenges in increasing competitiveness with other tourism. [Penelitian ini bertujuan untuk menganalisis eksistensi Wisata Batu Malin Kundang dalam persaingan destinasi pariwisata di Sumatera Barat melalui studi lapangan di kawasan Pantai Air Manis, Kota Padang. Hadirnya berbagai destinasi wisata baru yang berbasis wisata alam, dan spot visual modern menciptakan dinamika persaingan yang memengaruhi pola kunjungan para wisatawan. Maka, penting untuk mengkaji bagaimana destinasi wisata berbasis legenda dan budaya lokal dapat mempertahankan keberadaannya di tengah beragamnya wisata baru yang memperkenalkan keindahannya. penulis menggunakan pendekatan kualitatif deskriptif dengan metode studi lapangan. Data diperoleh melalui observasi langsung, wawancara dengan pedagang, masyarakat sekitar, dan wisatawan. Hasil penelitian menunjukkan bahwa, pertama,  eksistensi Batu Malin Kundang bertumpu pada kekuatan nilai budaya dan legenda yang memiliki legitimasi historis dalam masyarakat Minangkabau, kedua, daya tarik utama destinasi ini terletak pada aspek simbolik dan edukatif yang membedakannya dari destinasi wisata baru yang lebih berorientasi pada tren visual, ketiga, kekurangan wisata Batu Malin Kundang terletak dari sisi inovasi, promosi digital yang kurang aktif, fasilitas yang kurang bersih, harga sewa permainan yang tergolong mahal, dan maraknya aksi pungli. Kondisi inilah yang pada akhirnya menjadi tantangan dalam meningkatkan daya saing dengan wisata lain.]